1996
DOI: 10.1038/bjc.1996.414
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative approach to the distress caused by symptoms in patients treated with radical radiotherapy

Abstract: Summary A computerised self-assessment instrument was used to capture data on the distress caused by symptoms in 110 patients treated with radical radiotherapy. Patients selected symptoms from a list of 34 problems and then quantified the distress associated with each problem using a linear Analogue self assessment (LASA)-type scale. The test instrument was feasible: 90% of assessments were completed in under 14 min. There was a significant increase in tiredness and significant decrease in anxiety and worries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 26 publications
1
48
0
Order By: Relevance
“…In particular, cancer patients suffer from significant distress, tension, anxiety and feelings of helplessness especially before and at the beginning of radiotherapy (Munro and Potter, 1996;DeVries et al, 1998).…”
mentioning
confidence: 99%
“…In particular, cancer patients suffer from significant distress, tension, anxiety and feelings of helplessness especially before and at the beginning of radiotherapy (Munro and Potter, 1996;DeVries et al, 1998).…”
mentioning
confidence: 99%
“…Studies show that pain is one of the most frequently identified problems for people with lung cancer 189 or prostate cancer. 188 There is emerging evidence that pain arising from head and neck cancer can be severe and chronic, persisting beyond completion of treatment.…”
Section: Painmentioning
confidence: 99%
“…186 These include nausea and vomiting, 187 acute and chronic pain, [188][189][190] fatigue, 191,192 lymphoedema, [193][194][195][196][197] disfigurement, 109,111,198 odour, 199,200 incontinence, 201 cognitive problems, [202][203][204] difficulties in communication, 205 swallowing difficulties, 205 respiratory symptoms, 203,206 loss of appetite and nutritional deficiencies, 207,208 and fertility problems, [209][210][211] as well as a decline in general health.…”
Section: 3 P H Y S I C a L I S S U E Smentioning
confidence: 99%
“…Patients ranked sleep problems as the 5 th highest out of 14 distressing symptoms before their cancer treatment, and 4 th highest after cancer treatment [5]. In between 23% and 44% of cancer patients, sleep problems persist several years after the initiation of adjuvant therapy for cancer, suggesting that insomnia develops a chronic course in substantial numbers of cancer patients [6].…”
Section: Introductionmentioning
confidence: 99%